The Curriculum Of Arabic Education Program Of Bukittinggi Islamic State University In The Society 5.0 And MBKM - Zubaidah, Zubaidah; Hamid, M. Abdul; Syuhadak, Syuhadak; Amri, Ulil (Ijaz Arabi Journal of Arabic Learning, 2024)
The curriculum of a study program needs to be reviewed and evaluated at least once every two years so that it can be adapted to current needs and developments. Since technology and information develop very quickly, various aspects of life also develop, including education and educational curricula. Society 5.0 is all about technology, the development of the infrastructure, and skills that must be developed to utilize the technology with the aim of solving problems and the behaviors toward technology in solving problems.  Therefore, the curriculum of a study program must be adapted to the demands of society 5.0.  The MBKM (Merdeka Belajar Kampus Merdeka) curriculum as a curriculum that supports society 5.0 requires today’s students and lecturers to get out of their comfort zone by having additional skills in dealing with academic problems etc. For this reason, the Arabic Education program of Bukittinggi Islamic State University (UIN Bukittinggi) is obligated to redevelop and to review the existing curriculum that relevant with the developments and demands of the present days society.